Inequality and Support for Government Responses to COVID-19 - Hai-Anh Dang; Edmund Malesky; Cuong Viet Nguyen (Institute of Labor Economics (IZA), 2020)
Despite a rich literature studying the impact of inequality on policy outcomes, there has been limited effort to bring these insights into the debates about comparative support for government responses to the COVID-19 pandemic. We fill in this gap by analyzing rich survey data from six countries spanning different income levels and geographical locations — China, Italy, Japan, South Korea, the United Kingdom, and the United States. We find that poorer individuals are less supportive of government responses, and that poorest individuals are least supportive. Furthermore, poorer individuals residing in more economically unequal countries offer even less government support. We also find that both economic and non-economic factors could affect the poor's decisions to support stringent government policies. These findings suggest that greater transfers to the poor may ameliorate their resistance, increase support for strict policies, and may reduce the potential deepening of social inequalities caused by the pandemic.
Keywords: D0; H0; I3; O1; 330; COVID-19; inequality; income quintiles; poverty